2007
DOI: 10.1294/jes.18.153
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rates and Blood Lactate Response in Thoroughbred Horses during a Race

Abstract: We measured the heart rate before, during and after a 1200-m race, and blood lactate concentration at 10 min after a race in 23 Thoroughbred horses. The heart rate increased when horses were walking through the underground passage and after the jockeys mounted them in the paddock, even though there was no increase in exercise intensity. During the canter from the exit of the underground passage to the starting stalls, the heart rate increased to a peak value of 194.0 ± 2.0 (mean ± SE) beat/min, which was equiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 30 publications
1
22
1
Order By: Relevance
“…During exercise, lactate increases in the blood stream once the production exceeds its utilization and elimination (FERRAZ et al, 2008). The lactatemia observed in the present study was lower than the concentration found by MUKAI et al (2007), who evaluated exercise intensity in simulated races of 1200m on a sandy track with mean velocities of 15m s -1 and lactatemia of 22.5±0.6mmol L -1 .…”
Section: Discussioncontrasting
confidence: 77%
“…During exercise, lactate increases in the blood stream once the production exceeds its utilization and elimination (FERRAZ et al, 2008). The lactatemia observed in the present study was lower than the concentration found by MUKAI et al (2007), who evaluated exercise intensity in simulated races of 1200m on a sandy track with mean velocities of 15m s -1 and lactatemia of 22.5±0.6mmol L -1 .…”
Section: Discussioncontrasting
confidence: 77%
“…In comparing the effort exerted by horses in this training session of elite polo with other equestrian modalities and pointing out the changes in some variable such as pH, PCO 2 , lactate and glycaemia, similarities are noted with 3‐day event horses (Foreman et al . 1999) and racehorses (Davie and Evans 2000; Mukai et al . 2007).…”
Section: Discussionmentioning
confidence: 99%
“…2000). However, warm‐up routines usually performed in conjunction with Thoroughbred races in Japan, which increase heart rates ( HR ) of racehorses over 90% of their maxima (Mukai et al . 2007), are typically more intense than those described in previous studies of warm‐up effects (McCutcheon et al .…”
Section: Introductionmentioning
confidence: 99%